Current Practice of Clinical Electroencephalography. - Ebersole, John S. (Wolters Kluwer Health, 2002)
The standard-setting clinical electroencephalography textbook has been rewritten for the next decade of EEG technicians and resident and practicing neurologists. This Third Edition reflects the transition of the field to an all-digital environment, with fundamental changes in data recording, analysis, and interpretation. Drs. Ebersole and Pedley are outstanding educators with extensive experience in editing two of the leading journals-- Journal of Clinical Neurophysiology and Epilepsia, respectively.